KORELASI PEMBELAJARAN E-LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS 8 DI SMP NEGERI 14 KOTA BOGOR - Susetyaning Yuniar, Rizqi Dwi (Universitas Islam Negeri Alauddin Makassar, 2021)
Basically, e-learning is a learning process that is conveyed or facilitated by electronic technology, especially information and communication technology. Motivation is also an impetus that arises from within humans consciously or unconsciously to arouse their activities and cause good behavior to achieve their planned goals. Therefore, this study aims to determine how the correlation of e-learning learning to student learning motivation in class 8 Islamic education subjects at SMP Negeri 14 Bogor City. This study uses a quantitative approach with the correlation method. The data collection technique used in this study was a questionnaire. The subjects of this study were 85 students of class VIII at SMP Negeri 14 Bogor City. The data analysis technique used in this study is to use the correlation product moment, calculated using the help of SPSS Version 26. for Windows. Based on the results of the analysis, it is concluded that the correlation value of the X and Y variables is 0.406. Judging from the data interpretation, including moderate correlation. It means that the alternative hypothesis (Ha) is accepted and (Ho) is rejected. So there is a significant correlation between E-Learning Learning Against Student Motivation in Class 8 Islamic